A hole-filling gold paste for LTCC substrate and preparation method thereof
By using a specially made hole-filled gold paste on the LTCC substrate, the problems of flow, adhesion and depression at the bottom after filling are solved, and the high thixotropy, benign plasticity and excellent hole-filling performance of the gold paste are achieved, which significantly improves the The reliability of the substrate and the continuity of the pore column.
Patent Information
- Application Number
- CN202211001199.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-08-19
AI Technical Summary
The hole-filled gold paste of existing LTCC substrates is prone to flow, sticking and depression after drying after filling holes, which affects the reliability of the substrate and the continuity of the pores.
A fillered gold slurry for LTCC substrate is adopted, and its composition includes 85-95% gold powder, 0.3-2% Ca-B-Si system glass powder, 3.5-10% organic carrier, 0.1-1.5% inorganic additives and 0.1-1% surfactant, through specific preparation processes such as organic carrier preparation, glass powder preparation and gold paste preparation, to ensure high thixotropy, good plasticity and excellent hole filling performance of gold paste.
The prepared gold paste has no depression or flow after filling the holes, no adhesion at the bottom of the holes, and good contact with the hole wall after sintering, and no cracking, which significantly improves the reliability of the LTCC substrate and the continuity of the hole column.
Smart Images

Figure CN115424762B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrode slurry for LTCC, and in particular to a hole-filling gold slurry for LTCC substrate and a preparation method thereof. Background Art
[0002] LTCC (Low-Temperature Cofired Ceramic) is a low-temperature co-fired ceramic technology that makes low-temperature sintered ceramic powder into a green ceramic tape with precise thickness and density. The required circuit patterns are made on the green ceramic tape using laser drilling, slurry filling, printing and other processes, and multiple passive components (such as low-capacitance capacitors, resistors, filters, impedance converters, couplers, etc.) are buried in a multilayer ceramic substrate and then stacked together. The inner and outer electrodes can be made of metals such as Ag, Cu, and Au, respectively, and sintered at 800-900℃ to form high-density circuits that do not interfere with each other in three-dimensional space. It can also be made into a three-dimensional circuit substrate with built-in passive components. ICs and active devices can be mounted on its surface to make passive / active integrated functional modules, which can further miniaturize and increase the density of the circuit, making it particularly suitable for high-frequency communication components.
[0003] The main powder choices for the internal co-fired metal of the LTCC substrate are Cu, Ag and Au. Among them, Cu has a low cost, but needs to be sintered under nitrogen protection and needs to be matched with a specific raw tape. It is easily oxidized at high temperatures. Ag has the best conductivity and does not oxidize at high temperatures, but silver migration is prone to occur in high temperature, high humidity and extremely high voltage application scenarios, affecting the product life, thereby limiting its application in certain specific scenarios. It is widely used in substrates of consumer electronic products. The conductivity of Au is slightly worse than that of Cu and Ag, but due to its excellent stability, it does not oxidize or migrate, and the resulting LTCC substrate has good reliability. Its main application scenarios are high-precision and high-reliability circuits or multi-layer wiring fields such as military and avionics.
[0004] Conductive gold paste plays a decisive role in the reliability of the substrate as a key material in the LTCC substrate. There are some relevant studies on conductive gold paste in China. The patent publication number "CN113506648A" proposes "a kind of inner layer gold conductor paste for Ca-B-Si system LTCC", and publicly describes the preparation method of gold powder for conductive paste; the patent application publication number "CN113851251A" proposes "a transition hole filling paste for connecting the upper and lower gold and silver layers of the film strip in the LTCC substrate", and publicly describes the problem of inhibiting the silver migration of the gold and silver mixed paste. However, there is no relevant description on the hole filling performance of the gold paste. Since there are through holes of different sizes on a LTCC thin strip, the hole filling gold paste needs to be matched. Conventional gold paste is prone to problems such as bottom flow, adhesion and depression after drying after filling. After lamination, the continuity of adjacent hole columns is poor. At the same time, due to the different shrinkage rates of gold powder and substrate after sintering, if the paste and the thin strip material are not well matched, the hole column and the hole wall will be separated, which will affect the reliability of the substrate.
[0005] Therefore, it is necessary to provide a gold paste suitable for hole filling to solve the above problems. Summary of the invention
[0006] According to the above-mentioned requirements for the filling performance of through holes of different apertures in LTCC and the problems of sintering matching, a gold paste for filling holes in LTCC substrates and a preparation method are provided. The present invention mainly combines gold powder, glass powder, organic carrier, inorganic additive and 0.1-1% surfactant, and obtains a gold paste that meets the performance requirements through the preparation process of organic carrier preparation, glass powder preparation, batching, mixing, three-roll grinding, filtering and degassing. The prepared gold paste has the advantages of high thixotropy, good plasticity, excellent filling performance, no depression at the hole mouth after printing, no flow at the bottom of the hole, no bubbles in the hole, good contact with the hole wall after sintering, and no cracking.
[0007] The technical means adopted by the present invention are as follows:
[0008] A hole-filling gold paste for LTCC substrate, characterized in that the components are as follows by mass percentage:
[0009] Gold powder 85-95%;
[0010] Glass powder 0.3-2%;
[0011] Organic carrier 3.5-10%;
[0012] Inorganic additives 0.1-1.5%;
[0013] Surfactant 0.1-1%.
[0014] Furthermore, the particle size of the gold powder is 1 μm-3 μm, and the tap density is 7-10 g / cm3 , specific surface area 0.1-0.5m 2 / g.
[0015] Furthermore, the glass powder is a Ca-B-Si system glass powder, which is composed of several of CaO, B2O3, SiO2, Al2O3, BaO, and ZnO, and is prepared by a high-temperature melting-water quenching-air flow milling process. The powder prepared by the air flow mill has a relatively uniform particle size distribution, good product stability, and an average particle size of 1μm-2μm.
[0016] Furthermore, the organic carrier is composed of resin, organic solvent and thixotropic agent, the resin accounts for 15%-40% by mass of the organic carrier, the organic solvent accounts for 40%-60% by mass of the organic carrier, and the thixotropic agent accounts for 5%-30% by mass of the organic carrier.
[0017] Furthermore, the resin is ethyl cellulose.
[0018] Furthermore, the organic solvent is selected from one or more of terpineol, ethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, and alcohol ester dodecahydrate.
[0019] Furthermore, the thixotropic agent is selected from one or more of polyamide wax, polyethylene wax, modified hydrogenated castor oil, and fumed silica.
[0020] Furthermore, the inorganic additives are talcum powder and nano-SiO2.
[0021] Furthermore, the surfactant is an anionic or nonionic auxiliary agent, which plays a role in wetting and wrapping the gold powder in the slurry.
[0022] The present invention also discloses a method for preparing the hole-filling gold paste for LTCC substrates as claimed in the above claims, which is characterized by comprising the following steps:
[0023] S1. Preparation of organic carrier: weigh the solvent in a reaction kettle, turn the high-speed disperser speed to 800-1000 rpm for stirring, add the resin while stirring, and increase the speed to 2000-3000 rpm. At this time, under the action of high-speed shear, the temperature of the solvent and the resin rises to 70-80°C, and the resin begins to dissolve. Continue stirring for 15-20 minutes until the resin is completely dissolved. At this time, add the thixotropic agent and continue stirring for 15-20 minutes until the mixture forms a paste to obtain the organic carrier;
[0024] S2, glass powder preparation, weighing several of CaO, B2O3, SiO2, Al2O3, BaO, ZnO in a ball mill, adding a certain mass of zirconia balls, using a ball mill to mix evenly, pouring the mixture into a corundum crucible, melting at 1200°C for 1 hour, and pouring it into pure water after melting into a uniform glass liquid, placing the quenched glass residue in a 90°C oven to dry for 2 hours, and then grinding the dried glass residue into a glass powder with a particle size of 1μm-3μm through a jet mill;
[0025] S3, preparation of gold paste, weighing organic carrier, glass powder, gold powder, inorganic additives and surfactant in a container, setting the stirrer speed to 300rpm, mixing for 30min; grinding and dispersing the evenly mixed slurry with a three-roller mill for 6 times, filtering the ground gold paste with a 500-mesh nylon mesh, and then treating it with a vacuum degassing machine for 5-8min at a speed of 500-800rpm to obtain the hole-filling gold paste for LTCC substrate, the hole-filling gold paste fineness is less than 5μm, and the viscosity at 5rpm is 40-60Pa·s.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) At present, the gold powder used for gold paste is mainly prepared by chemical reduction method. The gold powder prepared by chemical reduction method has the characteristics of small particle size, more organic matter residue on the surface, small specific surface area, and difficult to coat, which leads to low viscosity and strong fluidity of the prepared gold paste. It is easy to flow after filling the holes and easy to stick to the bottom. According to the characteristics of gold powder, the present invention uses high-grade (N200, N300) ethyl cellulose in an organic carrier to wrap the gold powder, thereby increasing the viscosity of the slurry. At the same time, a higher proportion of thixotropic agent is introduced into the organic carrier. The prepared gold paste has high thixotropy and excellent plasticity. There is no dent after drying, and the flow can be effectively controlled. It is matched with anionic and non-ionic surfactants to reduce the viscosity and wire drawing type of the slurry. It has good hole filling performance and no adhesion between the bottom and the carrier plate.
[0028] (2) The glass powder of the present invention is specially made according to the characteristics of LTCC A6 thin strips, and is a Ca-B-Si system with good compatibility. At the same time, the powder is prepared by a jet mill process, and the particle size distribution is uniform, and there will be no local defects during sintering;
[0029] (3) The unique inorganic additives are added to the formula of the present invention. The addition of talcum powder can reduce the shrinkage rate during the sintering process of the gold paste. Nano-SiO2 has a large specific surface area, high sintering activity, and good adhesion to the pore wall. After sintering, there is no separation between the pore column and the pore wall.
[0030] In summary, the gold paste prepared by the present invention has the advantages of high thixotropy, good plasticity, excellent hole-filling performance, no depression at the hole mouth after printing, no flow at the hole bottom, no bubbles in the hole, good contact with the hole wall after sintering, and no cracking.
[0031] Based on the above reasons, the present invention can be widely promoted in the field of LTCC hole filling paste. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0033] Figure 1 This is a diagram showing the effect of hole filling in Example 3 of the present invention.
[0034] Figure 2 This is a slice diagram of the LTCC ceramic substrate after sintering using the gold paste filled holes of Example 3 of the present invention. DETAILED DESCRIPTION
[0035] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0036] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0038] The present invention provides a hole-filling gold paste for LTCC substrates, wherein the components are as follows by mass percentage:
[0039] Gold powder 85-95%, the particle size of the gold powder is 1μm-3μm, and the tap density is 7-10g / cm 3 , specific surface area 0.1-0.5m2 / g;
[0040] 0.3-2% glass powder, wherein the glass powder is a Ca-B-Si system glass powder, composed of several of CaO, B2O3, SiO2, Al2O3, BaO, and ZnO, and is prepared by a high-temperature melting-water quenching-air flow grinding process, with an average particle size of 1 μm-2 μm;
[0041] 3.5-10% of an organic carrier, the organic carrier is composed of a resin, an organic solvent and a thixotropic agent, the resin accounts for 15%-40% of the mass percentage of the organic carrier, and the resin is selected from ethyl cellulose; the organic solvent accounts for 40%-60% of the mass percentage of the organic carrier, and the organic solvent is selected from one or more of terpineol, ethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, and alcohol ester twelve; the thixotropic agent accounts for 5%-30% of the mass percentage of the organic carrier, and the thixotropic agent is selected from one or more of polyamide wax, polyethylene wax, modified hydrogenated castor oil, and fumed silica;
[0042] Inorganic additives 0.1-1.5%, talcum powder and nano-SiO2;
[0043] The surfactant is 0.1-1%, which is an anionic or non-ionic auxiliary agent and plays the role of wetting and wrapping the gold powder in the slurry.
[0044] Example 1
[0045] A hole-filling gold paste for LTCC substrate and a preparation method thereof are as follows:
[0046] S1. Preparation of organic carrier: 15 parts of terpineol and 45 parts of diethylene glycol butyl ether were weighed in a reaction kettle, and the high-speed disperser was turned on to 1000 rpm for stirring. 20 parts of ethyl cellulose STD-200 were added while stirring, and the speed was increased to 2500 rpm. At this time, under the action of high-speed shear, the temperature of the solvent and the resin increased to 70-80°C, and the resin began to dissolve. Stirring was continued for 18 minutes until the resin was completely dissolved, and 20 parts of modified hydrogenated castor oil were added. Stirring was continued for 15 minutes until the mixture formed a paste to obtain organic carrier A;
[0047] S2, glass powder preparation, weigh 33 parts of CaO, 23 parts of B2O3, 8 parts of SiO2, 15 parts of Al2O3, 13 parts of BaO, 8 parts of ZnO in a ball mill, add zirconium oxide balls, use a ball mill to mix for 30 minutes, pour the mixture into a corundum crucible, melt at 1200 ° C for 1 hour, melt into a uniform glass liquid, pour into pure water for water quenching, place the quenched glass residue in a 90 ° C oven for 2 hours, and then grind the dried glass residue into glass powder A through a jet mill. The average particle size is 1.8 μm;
[0048] S3, preparation of gold paste, weighing 6.8 parts of organic carrier A, 1 part of glass powder A, 90.5 parts of gold powder, 0.7 parts of talcum powder, 0.5 parts of nano-SiO2 and 0.5 parts of surfactant, setting the speed of the stirrer to 300rpm, mixing for 30min; using a three-roller mill to grind and disperse the mixed slurry for 6 times, filtering the ground gold paste with a 500-mesh nylon mesh, and then using a vacuum degassing machine for 6min, the speed is 600rpm, and the vacuum degassing treatment can reduce the bubbles and gaps generated during printing. That is, the hole-filling gold paste for LTCC substrates is obtained, the hole-filling gold paste fineness is less than 5μm, the viscosity is 320Pa·s at 0.5rpm, and the viscosity is 50Pa·s at 5rpm (Brookfield DV-III+P, CPA-52Spindle at 25℃).
[0049] Example 2
[0050] A hole-filling gold paste for LTCC substrate and a preparation method thereof are as follows:
[0051] S1, organic carrier preparation, weigh 25 parts of dipropylene glycol methyl ether, 25 parts of diethylene glycol butyl ether, 10 parts of alcohol ester twelve in a reactor, turn the high-speed disperser speed to 1000rpm for stirring, add 15 parts of ethyl cellulose STD-200 and 10 parts of ethyl cellulose STD-300 while stirring, and increase the speed to 2500rpm. At this time, under the action of high-speed shear, the temperature of the solvent and the resin rises to 70-80°C, and the resin begins to dissolve. Continue stirring for 20min until the resin is completely dissolved, add 10 parts of polyamide wax and 5 parts of fumed silica, and continue stirring for 18min until the mixture forms a paste to obtain an organic carrier B;
[0052] S2, glass powder preparation, weigh 35 parts of CaO, 32 parts of B2O3, 5 parts of SiO2, 18 parts of Al2O3, and 10 parts of BaO in a ball mill, add zirconium oxide balls, use a ball mill to mix for 30 minutes, pour the mixture into a corundum crucible, melt at 1200°C for 1 hour, melt into a uniform glass liquid, pour into pure water for water quenching, place the quenched glass residue in a 90°C oven for 2 hours, and then grind the dried glass residue into glass powder B through a jet mill. The average particle size is 1.6μm;
[0053] S3, preparation of gold paste, weighing 5.2 parts of organic carrier B, 0.8 parts of glass powder B, 92 parts of gold powder, 0.3 parts of talcum powder, 0.9 parts of nano-SiO2 and 0.8 parts of surfactant, setting the speed of the stirrer to 300rpm, mixing for 30min; using a three-roll mill to grind and disperse the evenly mixed slurry for 6 times, filtering the ground gold paste with a 500-mesh nylon mesh, and then using a vacuum degassing machine for 6min at a speed of 600rpm to obtain a hole-filling gold paste for LTCC substrates, with a hole-filling gold paste fineness of <5μm, a viscosity of 350Pa·s at 0.5rpm, and a viscosity of 45Pa·s at 5rpm (Brookfield DV-III+P, CPA-52Spindle at 25℃).
[0054] Example 3
[0055] A hole-filling gold paste for LTCC substrate and a preparation method thereof are as follows:
[0056] S1, preparation of organic carrier, weigh 7 parts of terpineol, 30 parts of diethylene glycol butyl ether, and 20 parts of diethylene glycol butyl ether acetate in a reaction kettle, turn the high-speed disperser speed to 1000 rpm for stirring, add 18 parts of ethyl cellulose STD-200 while stirring, and increase the speed to 2000 rpm. At this time, under the action of high-speed shear, the temperature of the solvent and the resin rises to 70-80°C, and the resin begins to dissolve. Continue stirring for 20 minutes until the resin is completely dissolved, add 20 parts of modified hydrogenated castor oil and 5 parts of fumed silica, and continue stirring for 20 minutes until the mixture forms a paste to obtain organic carrier C;
[0057] S2, glass powder preparation, weighing 20 parts of CaO, 29 parts of B2O3, 18 parts of SiO2, 8 parts of Al2O3, 15 parts of BaO, and 10 parts of ZnO into a ball mill, adding zirconium oxide balls, using a ball mill to mix for 30 minutes, pouring the mixture into a corundum crucible, melting at 1200°C for 1 hour, and pouring it into pure water for quenching after melting into a uniform glass liquid, placing the quenched glass residue in a 90°C oven for 2 hours, and then grinding the dried glass residue into glass powder C through a jet mill, and the average particle size was detected to be 1.8μm;
[0058] S3, preparation of gold paste, weighing 4.2 parts of organic carrier C, 0.5 parts of glass powder C, 94 parts of gold powder, 0.2 parts of talcum powder, 0.3 parts of nano-SiO2 and 0.8 parts of surfactant, setting the speed of the stirrer to 300rpm, mixing for 30min; using a three-roll mill to grind and disperse the evenly mixed slurry for 6 times, filtering the ground gold paste with a 500-mesh nylon mesh, and then using a vacuum degassing machine for 8min at a speed of 600rpm to obtain a hole-filling gold paste for LTCC substrates, with a hole-filling gold paste fineness of <5μm, a viscosity of 450Pa·s at 0.5rpm, and a viscosity of 50Pa·s at 5rpm (Brookfield DV-III+P, CPA-52Spindle at 25℃).
[0059] Comparative Example 1
[0060] Comparative Example 1 In the glass preparation of Example 1, the glass powder is replaced with Bi-B-Si system glass powder D, which is composed of 30 parts of Bi2O3, 25 parts of B2O3, 23 parts of SiO2, 5 parts of MgO, 8 parts of BaO, and 9 parts of ZnO.
[0061] Comparative Example 2
[0062] Comparative Example 2 is to remove the thixotropic agent polyamide wax from the organic carrier preparation of Example 2, and transfer its content to the solvent diethylene glycol butyl ether. The organic carrier is numbered D.
[0063] Comparative Example 3
[0064] Comparative Example 3 is to remove nano-SiO2 from the gold paste ratio of Example 3, and transfer its content to the organic carrier.
[0065] As shown in Table 1, the formulations of various embodiments and comparative examples are shown.
[0066] Table 1 Formulas of various embodiments and comparative examples
[0067]
[0068] After the gold paste was prepared, the viscosity of each embodiment and comparative example was tested, and the hole filling was performed on the LTCC A6 thin strip to compare the hole filling performance. The LTCC thin strip after hole filling was laminated and sintered (sintering peak temperature 880°C, total sintering time 150min), and the sintering matching was observed by slicing. Table 2 shows the various performance indicators of each embodiment and comparative example.
[0069] Table 2 Performance indicators of various embodiments and comparative examples
[0070]
[0071] like Figure 1 As shown, it can be seen that after the slurry prepared in Example 3 is filled in the hole, there is no depression, no diffusion at the bottom, and no adhesion after drying. Figure 2 As shown, there is no gap between the upper and lower hole columns after slicing, and no cracks on the hole wall.
[0072] From the comparison between Example 1 and Comparative Example 1, it can be seen that the gold paste using the glass powder system of the present invention has good matching with the pore wall of the porcelain body, and the cracking is effectively eliminated; from the comparison between Example 2 and Comparative Example 2, it can be seen that the organic system of the present invention is adopted, and the gold paste has high thixotropy and excellent printing and filling performance; from the comparison between Example 3 and Comparative Example 3, it can be seen that the addition of the inorganic additives defined in the present invention can effectively improve the adhesion of the gold paste to the pore wall after sintering.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A hole-filling gold paste for LTCC substrate, characterized in that: The mass percentage of each component is: Gold powder 85-95%, spherical gold powder particle size 1μm-3μm, tap density 7-10g / cm 3 , specific surface area 0.1-0.5m 2 / g; Glass powder 0.3-2%; 3.5-10% of organic carrier; the organic carrier is composed of resin, organic solvent and thixotropic agent, the resin accounts for 15%-40% of the mass percentage of the organic carrier, the organic solvent accounts for 40%-60% of the mass percentage of the organic carrier, and the thixotropic agent accounts for 5%-30% of the mass percentage of the organic carrier; the resin is ethyl cellulose; Inorganic additives 0.1-1.5%; the inorganic additives are talcum powder and nano-SiO2; Surfactant 0.1-1%; The specific preparation method comprises the following steps: S1. Preparation of organic carrier: weigh the solvent in a reaction kettle, turn the high-speed disperser speed to 800-1000 rpm for stirring, add the resin while stirring, and increase the speed to 2000-3000 rpm. At this time, under the action of high-speed shear, the temperature of the solvent and the resin rises to 70-80°C, and the resin begins to dissolve. Continue stirring for 15-20 minutes until the resin is completely dissolved. At this time, add the thixotropic agent and continue stirring for 15-20 minutes until the mixture forms a paste to obtain the organic carrier; S2, glass powder preparation, weighing several of CaO, B2O3, SiO2, Al2O3, BaO, ZnO in a ball mill, adding a certain mass of zirconia balls, using a ball mill to mix evenly, pouring the mixture into a corundum crucible, melting at 1200°C for 1 hour, and pouring it into pure water after melting into a uniform glass liquid, placing the quenched glass residue in a 90°C oven to dry for 2 hours, and then grinding the dried glass residue into a glass powder with a particle size of 1μm-3μm through a jet mill; S3, preparation of gold paste, weighing organic carrier, glass powder, gold powder, inorganic additives and surfactant in a container, setting the stirrer speed to 300rpm, mixing for 30min; grinding and dispersing the evenly mixed slurry with a three-roller mill for 6 times, filtering the ground gold paste with a 500-mesh nylon mesh, and then treating it with a vacuum degassing machine for 5-8min at a speed of 500-800rpm to obtain the hole-filling gold paste for LTCC substrate, the hole-filling gold paste fineness is less than 5μm, and the viscosity at 5rpm is 40-60Pa·s.
2. The gold paste for filling holes in LTCC substrate according to claim 1, characterized in that: The glass powder is a Ca-B-Si system glass powder, which is composed of several of CaO, B2O3, SiO2, Al2O3, BaO, and ZnO, and is prepared by a high-temperature melting-water quenching-air flow grinding process, with an average particle size of 1μm-2μm.
3. The gold paste for filling holes in LTCC substrate according to claim 1, characterized in that: The organic solvent is selected from one or more of terpineol, ethylene glycol butyl ether, propylene glycol butyl ether, dipropylene glycol methyl ether, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, and alcohol ester dodecahydrate.
4. The gold paste for filling holes in LTCC substrates according to claim 1, characterized in that: The thixotropic agent is selected from one or more of polyamide wax, polyethylene wax, modified hydrogenated castor oil and fumed silica.
5. The gold paste for filling holes in LTCC substrates according to claim 1, characterized in that: The surfactant is an anionic or nonionic auxiliary agent.
Citation Information
Patent Citations
Inner-layer gold conductor paste for Ca-B-Si system LTCC (Low Temperature Co-Fired Ceramic)
CN113506648A
Transition pore-filling slurry for connecting upper and lower gold and silver layers of film belt in LTCC (Low Temperature Co-Fired Ceramic) substrate
CN113851251A
Gold conductor wiring slurry co-fired with microwave dielectric ceramic at low temperature and preparation method of gold conductor wiring slurry
CN114783652A